Perancangan Front-end pada Sistem Informasi Kepegawaian Berbasis Aplikasi Android pada PT. XYZ - Fadhilah Roy Fasya; Evi Dwi Wahyuni; Briansyah Setio Wiyono (P3M Politeknik Negeri Banjarmasin, 2023)
Personnel information system is an application system that contains information from the staffing structure within a company. At PT. XYZ there are a problem regarding the personnel information system in the form of an attendance system, work target reports, and submission of payslips which were still manual. So that reporting from companies to employees is less effective and tends to be less transparent. Of the problems faced by PT. XYZ, an application based on Android mobile apps was created which has three main features, that is: attendance, reporting of daily work targets, and reporting of payslips. All of these features are listed in one application called